2015
DOI: 10.1016/j.virol.2015.09.011
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring the dynamics of emergence of a non-canonical recombinant of Tomato yellow leaf curl virus and displacement of its parental viruses in tomato

Abstract: Recombinant viruses are increasingly being reported but the dynamics of their emergence is rarely documented. A new recombinant Tomato yellow leaf curl virus (TYLCV-IS76) was detected for the first time in 2010 in Southern Morocco (Souss). An original diagnostic tool was needed to fit its unusual recombination profile. Although IS76 was detected following the appearance of Tylc symptoms on tolerant tomato plants, symptoms could not be associated to IS76 or to a synergy with criniviruses. According to infection… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
47
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(63 citation statements)
references
References 47 publications
5
47
0
Order By: Relevance
“…In contrast, Group 2 isolates appeared related to recently discovered Moroccan isolates from the El Jadida region. Our analyses suggested that the TYLCV isolates of Group 2 are derived from a Moroccan TYLCV-IS76 recombinant through a back recombination event, as previously suggested by Belabess et al (2015) for the El Jadida isolates [ 31 ]. This scenario, with a single recombination event leading to TYLCV-IS76 and a back recombination to generate the El Jadida TYLCV type, is consistent with field observations and experimental results which suggest that TYLCV-IS76 emergence is a rare event [ 42 ].…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…In contrast, Group 2 isolates appeared related to recently discovered Moroccan isolates from the El Jadida region. Our analyses suggested that the TYLCV isolates of Group 2 are derived from a Moroccan TYLCV-IS76 recombinant through a back recombination event, as previously suggested by Belabess et al (2015) for the El Jadida isolates [ 31 ]. This scenario, with a single recombination event leading to TYLCV-IS76 and a back recombination to generate the El Jadida TYLCV type, is consistent with field observations and experimental results which suggest that TYLCV-IS76 emergence is a rare event [ 42 ].…”
Section: Discussionsupporting
confidence: 80%
“…A second phylogenetic analysis was carried out in which additional sequences from databases were included ( Figure 2 B). Interestingly, in this tree, Group 2 sequences appeared to be closely related to two Moroccan sequences (LN846613 and LN846614) ( Figure 2 B), recently described by Belabess et al (2015) [ 31 ] for isolates sampled in the El Jadida (Morocco) region; note that these are nonrecombinant isolates [ 31 ]. To rule out a potential recombinant origin for Spanish isolates in Group 2 similar to the one originating TYLCV-IS76, both an alignment with TYLCV-IS76 and TYLCSV in the recombination region ( Figure 3 ), as well as an analysis of the sequences using the RDP4 program (data not shown) were carried out; no recombination events were identified.…”
Section: Resultssupporting
confidence: 70%
See 3 more Smart Citations